Relationship between alopecia areata and serum ferritin, TIBC and serum iron levels - Ramin Taheri (Majallah-i ̒Ilmī-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Simnān, 2011)
Introduction: Alopecia areata is a common disease that affects the life quality of patients. Iron deficiency has been suggested to play a role, but its effect is controversial. We decided to evaluate the relationship between alopecia areata and serum ferritin, TIBC and serum iron levels. Materials and Methods: In this study, 30 patients who were diagnosed with alopecia areata by a dermatologist and 30 healthy individual as the control group were evaluated. All the cases (patients and control group) were referred to Semnan Central Lab for the following laboratory tests: CBC test (WBC, HGB, PLT, MCV, MCH, MCHC), serum ferritin, serum iron and serum TIBC. Results: Mean serum ferritin (P<0.001), serum iron (P<0.001), transferin saturation (P<0.001) and mean hemoglobin (P=0.002) were significantly lower in patient group comparing to the control group. Mean TIBC (P<0.001) was significantly higher in patient group in compared with the control group (P<0.001). Conclusion: Our findings indicate that there is a relationship between alopecia areata and low serum ferritin, low serum iron and increased TIBC. Therefore evaluation of serum iron status and treatment, if needed, with iron supplements is recommended in alopecia areata patients .